Professoras primárias em Mato Grosso : trajetórias profissionais e sociabilidade intelectual na década de 1960 - Amorim, Rômulo Pinheiro de (2013)
This dissertation have to examine the emergence of a group of primary teachers as intellectuals of education in the state, based on an analysis of training courses and professional trajectories of these teachers during the 1960s and its implications for the organization's primary teaching of Mato Grosso.The definition of the 1960 period of study is justified by the fact that this is a decade in which the federal government have been elaborated policies, from the perspective of educational planning, searching to implement changes in education as a whole and, especially to prepare teachers for primary education, be it in courses of "recovery" for teachers "lay" to be in courses of "perfectioning" or "specialization" for the teachers “normalistas”. For this search, was elected the notion of the intellectual sociability and intellectual elaborated by Jean-François Sirinelli and the concepts of intelectual, intellectual field and the habitus formulated by Pierre Bourdieu to understand the professional trajectories of primary teachers of as belonging to the group of intellectuals of education of Mato Grosso. For to achievement this research have been consulted productions in the history of education related to the theme, as well as documents (reports, government messages, oral testimonies, newspapers) the files of the Diário Oficial of Mato Grosso, the Secretary of Education of Mato Grosso, the Public Archives of the State of Mato Grosso, the file the Nucleus of Information and Documentation of Regional History - NDIHR, Database Research Group in History Education and Memory - GEM / IE / UFMT and testimonies of primary teachers of who acted in the 1960s, collected especially for this research. Based on analyzes of routes for the formation and trajectories professionals primary teachers of and their relation with the state educational context of state, one can understand what happened during the 1960s, meaningful modifications in the formation deemed necessary for teachers of primary Mato-Grossense, both from the perspective of "recovery" as "perfecting" that affected the educational field configuration in Mato Grosso, introducing a new organization and new hierarchical relations in teaching primary in the state.